Upaya Meningkatkan Kemampuan Guru Dalam Mengoperasikan Aplikasi Selama Pembelajaran Daring Dan Luring Dimasa Pandemi Covid-19 di MI NW Nahdlatul Abrar Nyangget Sandubaya Mataram - Husaen Sudrajat (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2020)
This study aims to improve the ability of teachers to operate applications during online and offline learning during the Covid-19 pandemic. This research was conducted in several stages including planning, implementing, observing and reflecting, and this research was conducted by holding a workshop to increase the ability to operate the application. From the research results, it was found that prior to this workshop, teachers were not familiar with various applications that could be used in the teaching and learning process. This is known from the results of unstructured interviews with research subjects. Meanwhile, after the workshop, it was found that teachers knew and could even operate applications that could be used in the teaching and learning process, especially during the Covid-19 pandemic online and offline. So it can be concluded that the existence of a workshop to increase the ability of teachers to operate learning applications really helps teachers in planning online and offline learning during the Covid-19 pandemic.